Specialization of the Geomorphometric Concepts in Digital Elevation Models - Quintero, Rolando; Torres, Miguel; Menchaca-Mendez, Rolando; Moreno-Ibarra, Marco; Guzman, Giovanni; Cortez, Paola (International Journal of Combinatorial Optimization Problems and Informatics, 2012)
According to the perception that subjects have about geographic objects, people can evaluate their proximity. The answers to the question if a geographic object is near other will be different according to the environment that the objects belong to. Also, when we consider geographic objects that do not have well defined boundaries, the perceptions of people with respect to the distance will be very different. This work focuses on determining the proximity relationships between geomorphological objects such as mountains and plains in order to find composite geomorphometric objects based on their semantic description. The paper describes a methodology in which we propose the use of relations between geomorphological objects to determine if an area (semantically described) can be considered as a "valley". We particularize the distance metric in the application domain of the landforms by applying polls that allow us to obtain the perception of people about the proximity.